An Investigation of Teachers’ and Students’ Value Perceptions Through Heroic Figures - Fatma Budak; Süreyya Gürses (Uluslararası Türk Eğitim Bilimleri Dergisi)
This study aims to reveal the value perceptions of primary school students and their classroom teachers through the heroes they associate with core values. Within the framework of social learning theory, the influence of role model figures on children's value acquisition processes is emphasized. Conducted within the scope of a descriptive survey model, the research collected data from 236 students in the 3rd and 4th grades and 12 teachers working in these classes during the 2023–2024 academic year. Participants were asked to write the name of a hero they associate with each of the ten core values determined by the Ministry of National Education. The collected data were analyzed using the descriptive analysis method, and the findings were classified based on the heroes’ domains of activity, gender, grade level, and a comparison between teachers and students. The results indicate that students most frequently associated values with Atatürk, cartoon characters, and individuals from their close environment, whereas teachers placed greater emphasis on historical and religious figures. Notably, the prominent presence of media characters in children's value perception is striking. This finding suggests that values education must be reconsidered with new strategies suited to the digital age.